Islamophobia in Context of Freedom of Speech: A Critical Analysis of Media Representation - Sultana, Munazza (Journal of Islamic and Religious Studies, 2022)
This study focuses on the impact of Islamophobia on Muslim youth. Islamophobia is, nowadays, a much-used but little understood term that is universally accepted by worldwide governments and international organizations. The study also highlights the spread of Islamophobia through media and its effect on Muslim youth residing all over the world. Phobia is an irrational fear of something so Islamophobia is synonymous with fear and anxiety against Muslims. No group is left unaffected by the effects of Islamophobia, a threat to one is a threat to all. In this study, critically analyze the role of media and Islamophobia by studying the various research studies and books. It has been analyzed that media representation is the major cause of the spread of Islamophobia. Youngsters in different parts of the world face verbal assaults. The major problems they face lie in the sectors of education, job, and employment, physical appearances, housing, and residence, stereotyping as well as domestic violence. Thus, by collaborating with the government, Islamic organizations, and higher education institutions, the media can be a tool or tactic to combat the upheaval of Islamophobia.